Effect of a separate heater structure for crystallisation to enable multilevel storage phase-change memory. (21st April 2014) - Alip, Rosalena Irma; Mohamad, Zulfakri; Yin, You; Hosaka, Sumio
The effect of a separate-heater structure for crystallisation to enable multilevel storage for phase-change memory (PCM) device was investigated. This separate-heater is characterised by a constant resistant R h . Existing power from the heater layer (TiSi3 ) can be well controlled, enabling crystallisation process for multilevel storage. Ge2 Sb2 Te5 (GST) was used as the memory layer. A simulation using COMSOL 3.2 was done to study the temperature distribution in the GST layer by applying an SET pulse ranging from 0 V to 3 V directly to the heater layer. The temperature of the GST layer increased gradually with increasing pulse amplitude, making multilevel storage possible due to the gradual resistance drop. For experimental work, when an increasing pulse amplitude at 100 ns pulse width was applied to the separate heater layer, resistance in the memory layer dropped gradually for more than three orders of magnitude. This indicates that the existing power from the separate heater was well controlled for efficient crystallisation in the memory layer, GST, enabling multilevel storage. The reproducibility of the device was also investigated by applying a RESET pulse directly to the GST layer. A PCM device with a separate-heater structure is stable and has the ability to reproduce more than two cycles.